Mass recovery of carbonated fabrics of glass fibres after isothermal heating - Pentjuss, E.; Balodis, J.; Vdovicenko, M.; Gabrusenoks, Jevgenijs; Bajars, Gunars; Petersone, L.; Kleperis, Janis (Institute of Physics Publishing, 2019)
Leaching of Na+ ions in sodium oxide (Na2O) and silica (SiO2) containing glass is well investigated mainly due to its weak weathering. The object of this study was naturally (at room conditions) leached, steady state product on surface of sodium oxide-silica-alumina (Al2O3) glass fibers (in fabric) in a form of shell of "glyed" trona crystals as a result of interaction of leached Na+ ions and H2O and CO2 from atmosphere. There are presented results of continued former investigation of mass loss by isothermal heating of fabric and mass recovery in different atmospheres during the first phase of adsorption (at least 0.25h) without changes of state of crystals obtained during preheating at different temperatures. There are observed two ways of decomposition of trona (Na3H (CO3)2•2H2O) with its beginning at about 55-570C and 73-750C. The regression analysis of mass restoring in different atmospheres indicates to simultaneous and exponential mass increase by physical adsorption of CO2 and H2O having the different parameters of exponents vs time. Decomposition of trona is discussed in terms of parameters of exponent vs preheating temperature.
Acknowledgement: Authors acknowledge financial support from Latvian National Program IMIS2
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics